An overview of the most threating diseases that affect worldwide citriculture: Main features, diagnose, and current control strategies - Barbieri, Hellen Bertoletti; Fernandes, Laura Soler; Pontes, João Guilherme de Moraes; Pereira, Alana Kelyene; Fill, Taicia Pacheco (Frontiers in Natural Products, 2023)
Citriculture has been one of the most important agricultural activities worldwide. Brazil is among the five major citrus producers in the world, together with China, the European Union (EU), the United States, and Mexico. Together, these five groups are responsible for about 50% of the global citrus fruit production and this industrial segment is responsible for generating direct and indirect jobs. However, several citric diseases such as citrus canker, huanglongbing, citrus variegated chlorosis, and citrus black spot have been associated with annual losses of tons of fruits and orange trees impacting the global economy for decades. Citrus canker is caused by the gram-negative bacteria Xanthomonas citri subsp. citri. and is associated with symptoms such as the formation of chlorotic rings in the leaves, stems, and fruits. Huanglongbing (HLB) is mainly associated with the gram-negative bacteria Candidatus Liberibacter spp. and its main symptoms are the appearance of yellowish branches and deformed small leaves with yellowish spots. Citrus variegated chlorosis (CVC) is associated with the bacterium Xylella fastidiosa and causes chlorotic spots with irregular edges on leaves and deformation of new leaves. Citrus black spot (CBS) is caused by the fungus Phyllosticta citricarpa and generates lesions on fruits and reddish-brown leaf lesions. Since citrus is important for global agriculture, the current review addresses the main features of these important diseases including their symptoms and transmission, as well as the diagnosis and control strategies that have been studied so far for application in the field.